Multiscale Modeling of Non-Local Damage Evolution in Lithium-Ion Batteries. (7th July 2017) - Behrou, Reza; Maute, Kurt
Abstract : We present a multi-scale finite element model to study damage evolution in electrode active particles. The electrochemical and mechanical phenomena in the separator and the porous electrode, composed of solid active materials and liquid electrolyte, are described by a multi-scale finite element model. The evolution of damage in the electrode active particles, caused by diffusion-induced stresses, is described by a non-local damage evolution model. To model the influence of damage evolution on transport properties and the electrochemical performance of the battery, the diffusivity of electrode active particles is described in terms of damage evolution parameters. The results of numerical studies suggest that damage evolution in the electrode active particles causes significant capacity fade and reduction in the electrochemical and mechanical performance of the battery. The results of uniform and non-uniform micro-scale particle sizes in the cathode layer show that significant capacity fade occurs when uniform particle sizes are considered.